2011
DOI: 10.1007/s11012-011-9433-1
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet analysis for the characterization of forward-directivity pulse-like ground motions on energy basis

Abstract: The characterization of the prominent features of near-fault pulse-like ground motions is under scrutiny. Relationships between pulse characteristics and the performance of structures are here established. Two wavelet energy-based signal processing procedures are introduced. The aim is the construction of simplified signals containing the prominent features of the data distribution recorded from pulse-like earthquakes; signals that can be efficiently used in the design of civil engineering structures, increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…When the structure is located within an area close to the seismic fault, eg, within 30 km, 1 particularly high seismic demands are usually imposed. From the seismological perspective, numerous studies have been carried out by using analytical models to characterize the velocity pulses, [4][5][6] accounting for the pulse effects in seismic hazard analysis, 7,8 simulating pulse-like ground motions using stochastic approaches, 9,10 and classifying velocity pulses through automated algorithms. In contrast, the damage resulting from far-field ground motions is typically caused by the repeated cycles of inelastic deformation that accumulates in the structural components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the structure is located within an area close to the seismic fault, eg, within 30 km, 1 particularly high seismic demands are usually imposed. From the seismological perspective, numerous studies have been carried out by using analytical models to characterize the velocity pulses, [4][5][6] accounting for the pulse effects in seismic hazard analysis, 7,8 simulating pulse-like ground motions using stochastic approaches, 9,10 and classifying velocity pulses through automated algorithms. In contrast, the damage resulting from far-field ground motions is typically caused by the repeated cycles of inelastic deformation that accumulates in the structural components.…”
Section: Introductionmentioning
confidence: 99%
“…3 During the past two decades, near-fault pulse-like ground motions have been extensively studied by the seismology and earthquake engineering communities. From the seismological perspective, numerous studies have been carried out by using analytical models to characterize the velocity pulses, [4][5][6] accounting for the pulse effects in seismic hazard analysis, 7,8 simulating pulse-like ground motions using stochastic approaches, 9,10 and classifying velocity pulses through automated algorithms. [11][12][13] From the engineering perspective, the effects of pulse-like ground motions on various structures have been investigated, including idealized single (or multi)-degree-of-freedom (SDOF) systems, 14,15 seismically base-isolated structures, 16,17 bridge structures, 18,19 and some other special buildings or elements.…”
Section: Introductionmentioning
confidence: 99%
“…Baker (2007) adopted continuous wavelet transform to extract velocity pulse and proposed a quantitative identification criterion for classifying one target ground motion as pulse-type or non-pulse-type. Yaghmaei-Sabegh (2010, 2012, Mollaioli (2012) and Xie et al (2012) have made some further researches based on the method of Baker (2007). Ghahari et al (2010) extracted velocity pulse using a decomposion method named "moving average filtering".…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that at locations close to the fault, forward directivity may produce large-amplitude velocity pulses, which may affect the response of structures [19][20][21][22][23][24][25]. In particular, Priestley [26] observed that in the presence of velocity pulses the effectiveness of damping might be reduced.…”
Section: Introductionmentioning
confidence: 99%